Inclusive education: A path to equal rights - Romanova, Galina A.; Ananishnev, Vladimir M.; Darda, Ekaterina S. (Opción, 2020)
The aim of the study is the introduction of inclusive education in order to help students with special educational needs as a path to equal rights via SWOT, PEST and PESTLE analyses. As a result, the number of children with disabilities in underpopulated areas is smaller in countries with low population density than in small densely populated countries. In conclusion, the alternative ways to increase the effectiveness of the inclusive approach to the education system have been proposed based on the extension of distance learning methods and the development of incentive mechanisms for educational process participants